Pengaruh Academic Self-Efficacy dan Dukungan Sosial Terhadap Academic Burnout - Pravesti, Cindy Asli; Wulandari, Cindy Ayu (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
This study aimed to examine the relationship between academic self-efficacy and social support on learning burnout among students in Sidoarjo. Involving 160 participants, this quantitative research utilized three measurement instruments: an academic self-efficacy scale, a social support scale, and a learning burnout scale. Data were analyzed using multiple linear regression with SPSS version 26.0, following classical assumption tests including normality, heteroscedasticity, and multicollinearity tests. The results revealed a positive and significant correlation between academic self-efficacy and social support (r = 0.692; p = 0.000). However, the correlation between academic self-efficacy and learning burnout was negative but not statistically significant (r = -0.034; p = 0.797). Simultaneous analysis indicated that academic self-efficacy and social support collectively had a significant effect on learning burnout (F = 58.920 > F table = 3.05; p = 0.000), contributing 27.2% to the variance in burnout levels. Thus, while academic self-efficacy alone did not significantly predict learning burnout, the two variables together played an important role in explaining students’ burnout. These findings underscore the importance of fostering a supportive learning environment and strengthening students' academic self-efficacy to mitigate burnout in the learning process.____________________________________________________________________Penelitian ini bertujuan untuk mengkaji hubungan antara keyakinan akademik dan dukungan sosial terhadap kejenuhan belajar pada peserta didik di Sidoarjo. Melibatkan 160 pelajar, studi kuantitatif ini menggunakan tiga skala pengukuran dan dianalisis melalui regresi linier berganda dengan bantuan SPSS versi 26.0. Hasil menunjukkan adanya hubungan positif dan signifikan antara keyakinan akademik dan dukungan sosial (r = 0,692; p = 0,000). Namun, korelasi antara keyakinan akademik dan kejenuhan belajar bersifat negatif tetapi tidak signifikan (r = -0,034; p = 0,797). Analisis simultan memperlihatkan bahwa keyakinan akademik dan dukungan sosial secara bersama-sama berpengaruh signifikan terhadap kejenuhan belajar (F hitung = 58,920 > F tabel = 3,05; p = 0,000), dengan kontribusi sebesar 27,2%. Dengan demikian, meskipun secara individu pengaruh keyakinan akademik terhadap kejenuhan tidak signifikan, secara kolektif kedua variabel ini memiliki peran penting dalam menjelaskan tingkat kejenuhan belajar. Temuan ini menekankan pentingnya membangun lingkungan belajar yang mendukung serta memperkuat keyakinan akademik untuk mengurangi kejenuhan dalam proses pembelajaran.